Managing healthcare worker well‐being in an Australian emergency department during the COVID‐19 pandemic. (25th June 2020) - Poonian, Jasmine; Walsham, Nicola; Kilner, Thomas; Bradbury, Elizabeth; Brooks, Kristen; West, Emma
Abstract: Emergency Medicine staff in Australia and New Zealand are at the forefront of the healthcare response to COVID‐19. This article describes a well‐being plan for ED staff that has been devised to mitigate against the negative psychological impact of the COVID‐19 pandemic.